Diseño e implementación de un prototipo de medidor inteligente de energía eléctrica para consumos residenciales - Andrade Guerrero, Adonis Gabriel (2022)
This project aims to implement a smart meter for measuring the consumption of electrical energy in residences, which coordinates the ability to reflect the energy consumed. The development of the intelligent measurement system allows residential users to know the daily and monthly electricity consumption, which will be displayed on a digital screen. Furthermore, electrical parameters such as voltage (V), electric current (A), offs set and power angle (kW), are measurements that can be easily interpreted by any resident. Electric companies use electromechanical and mechanical meters to measure residential electrical energy consumption and are the only ones that can measure consumption. For this reason, this project will be carried out to allow the user manages the energy measurements of the electrical network connected to the house to verify fair billing and energy savings by consumption verification in the electrical spreadsheets. Consequently, it was proposed as an alternative to improve the assortment of measurement information, implementing a new smart metering system that will allow residential users to know the consumption of electrical energy, have active participation in the improvement of energy resources, changes in demand, greater flexibility of the meter for its proper use. For the design, different factors were analyzed, such as: economic and technical.